Deterrence versus intrinsic motivation: Experimental evidence on the determinants of corruptility - Günther G. Schulze; Björn Frank (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2000)
This paper reports on an experiment of corruption that was conducted in two treatments: one with the possibility of detection and one without. It turns out that monitoring reduces corruption through deterrence; at the same time, it destroys the intrinsic motivation for honesty. Thus the net effect on overall corruption is a priori undetermined. We show that the salary level has an influence on corruption through increased opportunity costs of corruption, but fail to find evidence for a loyalty effect. Interesting policy conclusions emerge.
Keywords: C91; D82; 330; corruption; gender; intrinsic motivation; reciprocity